Trade Shocks and the Provision of Local Public Goods - Leo Feler; Mine Zeynep Senses (Institute for the Study of Labor (IZA), 2016)
We analyze the impact of trade-induced income shocks on the size of local government, and the provision of public services. Areas in the US with declining labor demand and incomes due to increasing import competition from China experience relative declines in housing prices and business activity. Since local governments are disproportionately funded through property and sales taxation, declining property values and a decrease in economic activity translate into less revenue, which constrains the ability of local governments to provide public services. State and federal governments have limited ability to smooth local shocks, and the impact on the provision of public services is compounded when local income shocks are highly correlated with shocks in the rest of the state. The outcome is greater inequality not only in incomes but also in the quality of public services and amenities across US jurisdictions.
Keywords: F14; F16; H41; H70; R12; R23; 330; trade shocks; housing prices; intergovernmental transfers; public finance; public goods